Volume 2: Biomedical and Biotechnology 2012
DOI: 10.1115/imece2012-88081
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Muscle Models: The Role of Oscillatory Behavior in Force Control

Abstract: This paper presents the analysis of a third-order linear differential equation representing a muscle-tendon system, including the identification of critical damping conditions. We analytically verified that this model is required for a faithful representation of muscle-skeletal muscles and provided numerical examples using the biomechanical properties of muscles and tendon reported in the literature. We proved the existence of a theoretical threshold for the ratio between tendon and muscle stiffness above whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The presence of a tendon elastic element favors an oscillatory response to external disturbances that normally needs to be eliminated [9]. We demonstrated that a higher order model always exhibits an oscillatory free response and cannot be critically dampened for mechanical parameters included within the normal physiological range.…”
Section: Introductionmentioning
confidence: 89%
“…The presence of a tendon elastic element favors an oscillatory response to external disturbances that normally needs to be eliminated [9]. We demonstrated that a higher order model always exhibits an oscillatory free response and cannot be critically dampened for mechanical parameters included within the normal physiological range.…”
Section: Introductionmentioning
confidence: 89%
“…The ratio between muscle stiffness and rigidity of the connective tissue has been reported to vary between 1:1 and 1:10 [2124]. …”
Section: Methodsmentioning
confidence: 99%
“…(4) so to achieve five equally spaced reflex gains levels. Literature reported ratios between Kmlevel and α to vary between 1 and 10 [2831]. Since we assumed the intrinsic muscle stiffness α to be Kmlevel/4, the variation of Kmlevel following eq.…”
Section: Methodsmentioning
confidence: 99%